2018
DOI: 10.20944/preprints201810.0283.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geomorphology and Altitude Effects on Diversity and Structure of Vanishing Montane Forest of Southern Ecuador

Abstract: 1) Background: Neotropical montane forests represent one of the most diverse ecosystems; however, they are also the most threatened for deforestation. Our main goal is to evaluate the change in Basal Area (BA), Density and Species Composition of montane forests in the southern Ecuador and to determine the influence on some critical ecological and geomorphological factors. 2) Methods: One hundred thirty-two temporary plots of 400 m2 each were installed; we identified and measured all trees> 10 cm DBH. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
1
1
0
1
Order By: Relevance
“…Overall, these figures also compare well to those reported for high Andean forest ecosystems (2,300–2,900 m) in Southern Ecuador by Cabrera et al. (2019), who used a higher DBH threshold (10 cm) and obtained about 21 tree species and an average value of 2.44 for Shannon's diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, these figures also compare well to those reported for high Andean forest ecosystems (2,300–2,900 m) in Southern Ecuador by Cabrera et al. (2019), who used a higher DBH threshold (10 cm) and obtained about 21 tree species and an average value of 2.44 for Shannon's diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Anthropogenic disturbances have influenced vegetation in tropical forests of the Philippines particularly in GMPLRS. Human disturbances are widely believed to reduce species richness in tropical forest landscapes (Buot and Osumi 2011;Sopsop and Buot 2013;Nguyen et al 2015;Imani et al 2016; Van and Cochard 2017;Cabrera et al 2018;Gilbert et al 2020), as observed in the disturbed plots, such as GUI 08 (lowest elevation) and GUI 01 (highest elevation) (see Table 4). The results of this study agree with the findings of Sopsop and Buot (2013) in the Aborlan Guba System, that the lowest and highest portions of the forest experienced the greatest degree of human disturbance, with the former heavily impacted by kaingin farming or shifting cultivation and the latter by clearing due to resource harvesting.…”
Section: Environmental Variables Influencing the Typical Physiognomy ...mentioning
confidence: 99%
“…En el Nivel 1 se presentaron cuatro especies de Pinus. Es importante señalar que la presencia y patrones de la vegetación a lo largo de los gradientes altitudinales se generan debido a la interacción compleja de diversos factores tales como la altitud, la exposición a la radiación solar y la posición topográfica de las poblaciones vegetales, entre otros elementos observables (Girardin et al, 2014;Jadán et al, 2017;Cabrera et al, 2019).…”
Section: Características Dasométricasunclassified